2022
DOI: 10.1111/dpr.12595
|View full text |Cite
|
Sign up to set email alerts
|

Offline contexts of online jobs: Platform drivers, decent work, and informality in Lagos, Nigeria

Abstract: Motivation:The Sustainable Development Goals targets include decent work for all by 2030 but progress in sub-Saharan Africa has been slow. Over the past five years, the platform work sector (e-hailing platforms in particular) has expanded considerably on the continent, providing work opportunities to the growing urban populations. The quality of this work, however, is heavily contested. Purpose: We deepen and extend our understanding of the gig economy in sub-Saharan Africa and assess its potential for creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…It can take the form of controlling the competition among workers for jobs or tasks, controlling how the work is done, placing barriers between the gig worker and the client, and contractually enforcing the removal of some rights from the gig worker (Spitko, 2020). Platform design and operation, pervasive monitoring and surveillance, the rating and evaluation systems, the tendency to value the client over the worker (Chan, 2022), and the distributed nature of gig work make it difficult for workers to gain any type of significant bargaining power and when they do, it is characterized by power asymmetry tilted in favor of the platform (Cieslik et al, 2022; Zhu & Marjanovic, 2021). Fleitoukh and Toyama (2020) provide a clear summary of the core issue “[t]he bargaining power of the worker is truncated when operating through a digital tool” (p. 3).…”
Section: Resultsmentioning
confidence: 99%
“…It can take the form of controlling the competition among workers for jobs or tasks, controlling how the work is done, placing barriers between the gig worker and the client, and contractually enforcing the removal of some rights from the gig worker (Spitko, 2020). Platform design and operation, pervasive monitoring and surveillance, the rating and evaluation systems, the tendency to value the client over the worker (Chan, 2022), and the distributed nature of gig work make it difficult for workers to gain any type of significant bargaining power and when they do, it is characterized by power asymmetry tilted in favor of the platform (Cieslik et al, 2022; Zhu & Marjanovic, 2021). Fleitoukh and Toyama (2020) provide a clear summary of the core issue “[t]he bargaining power of the worker is truncated when operating through a digital tool” (p. 3).…”
Section: Resultsmentioning
confidence: 99%
“…According to the authors of this article, a very important observed research area is the issue of decent work. In this area, scientific inquiries aimed at analyzing the potential of the gig economy for the creation of decent work are discernible (Cieslik et al, 2022), or the issue of decent working conditions for non-standard workers is raised (Loganathan, 2022). It should be emphasized at this point that one of the extremely important elements determining decent work and raised by researchers is the issue of decent working time (Rodrigues et al, 2021).…”
Section: Keyword Co-occurrence Clusters Presented Inmentioning
confidence: 99%
“…Therefore, platforms are usually seen as replacing the full‐time stable employment of the postwar era with new low‐quality and vulnerable jobs, especially in the Global North (De Stefano, 2016; Munck et al, 2020). Furthermore, as a global trend, platform work is found exacerbating the already vulnerable labour conditions of informal workers, and even promoting the movement of formal workers into informal arrangements (Cieslik et al, 2021; ILO, 2021; World Bank, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%